2020
DOI: 10.1177/1744806920930858
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of GRK6 in arcuate nucleus promotes chronic visceral hypersensitivity via NF-κB upregulation in adult rats with neonatal maternal deprivation

Abstract: Aims The arcuate nucleus is a vital brain region for coursing of pain command. G protein-coupled kinase 6 (GRK6) accommodates signaling through G protein-coupled receptors. Studies have demonstrated that GRK6 is involved in inflammatory pain and neuropathic pain. The present study was designed to explore the role and the underlying mechanism of GRK6 in arcuate nucleus of chronic visceral pain. Methods Chronic visceral pain of rats was induced by neonatal maternal deprivation and evaluated by monitoring the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
4
5
0
Order By: Relevance
“…The CRD threshold of NMD rats was significantly reduced when compared with CON ( Figure 1A , *** P < 0.001, Tukey post hoc test following two-way repeated-measures ANOVA). The data confirms the idea again that NMD might develop chronic visceral hyperalgesia in adult rats (Xiao et al, 2016 ; Du et al, 2019 ; Li et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The CRD threshold of NMD rats was significantly reduced when compared with CON ( Figure 1A , *** P < 0.001, Tukey post hoc test following two-way repeated-measures ANOVA). The data confirms the idea again that NMD might develop chronic visceral hyperalgesia in adult rats (Xiao et al, 2016 ; Du et al, 2019 ; Li et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
“…Chronic visceral pain was induced by NMD, as described previously (Du et al, 2019 ; Li et al, 2020 ). In short, from the 2 to 15 days of birth, the newborn SD male pups of the NMD group were placed in a separate box with an electric blanket for 3 h. After the separation period, the pups were placed back with their dams.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have also shown that changes in expression and functions of key ion channels and receptors in extrinsic sensory neurons play an important role in the abnormal pain of gastrointestinal diseases. [14][15][16] Acid-sensing ion channels (ASICs) are a class of cation channels that are directly activated by extracellular acids and belong to the degenerate protein, epithelial Na + ion channel superfamily (DEG/ENaC), which are widely distributed in central and peripheral nervous systems. 17 ASICs are divided into at least six isoforms: ASIC1a, ASIC1b, ASIC2a, ASIC2b, ASIC3, and ASIC4.…”
Section: Introductionmentioning
confidence: 99%